27*x3=(x+2)3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\Leftrightarrow x\left(x-5\right)\left(x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=5\\x=-5\end{matrix}\right.\)
a)
=(x-2)3
b)\(\left(2-x\right)^3\)
c)\(\left(x+\dfrac{1}{3}\right)^3\)
d)\(\left(\dfrac{x}{2}+y\right)^3\)
e)
\(=\left(x-1\right)^2\left(x-1-15\right)+25\left[3\left(x-1\right)-5\right]\)
\(=\left(x-1\right)^2\left(x-16\right)+25\left(3x-3-5\right)\)
\(=\left(x-1\right)^2\left(x-16\right)+25\left(3x-8\right)\)
\(3^2.3^x.81-27^4=0\)
\(3^2.3^x.3^4-\left(3^3\right)^4=0\)
\(3^6.3^x-3^{12}=0\)
\(3^6.3^x-3^{12}=0\)
\(3^6.3^x=0+3^{12}\)
\(3^6.3^x=3^{12}\)
\(3^{6+x}=3^{12}\)
\(\Rightarrow6+x=12\)
\(x=12-6\)
\(\Rightarrow x=6\)
\(a,\Rightarrow x=3\)
\(b,\Rightarrow2x-1=2\)
\(\Rightarrow2x=3\)
\(\Rightarrow x=\dfrac{3}{2}\)
\(c,\Rightarrow x-2=4\)
\(\Rightarrow x=6\)
\(d,\Rightarrow2x-3=3\)
\(\Rightarrow2x=6\)
\(\Rightarrow x=3\)
\(a,\left(x-36\right):\left(2\cdot3^2\right)=2^3\cdot3\\ \Leftrightarrow x-36=432\\ x=468\\ b,2^x=32\\ \Leftrightarrow x=5\\ \Leftrightarrow x^3=27\\ \Leftrightarrow x^3=3^3\\ \Leftrightarrow x=3\\ d,1579+\left(625-x\right)=2023\\ \Leftrightarrow x=1579+625-2023\\ \Leftrightarrow x=181\)
A. \(\left(x-36\right):\left(2.3^2\right)=2^3.3\)
\(\left(x-36\right):\left(2.9\right)=8.3\)
\(\left(x-36\right):18=24\)
\(x-36=24.18\)
\(x-36=432\)
\(x=432+36\)
\(x=468\)
B. \(2^x=32\)
\(2^x=2^5\)
\(x=5\)
C. \(x^3=27\)
\(x^3=3^3\)
\(x=3\)
D. \(1579+\left(625-x\right)=2023\)
\(625-x=2023-1579\)
\(625-x=444\)
\(x=625-444\)
\(x=181\)
a) (2x−1)2−25=0(2x−1)2−25=0
(2x−1)2=0+25=25(2x−1)2=0+25=25
(2x−1)2=52=(−5)2(2x−1)2=52=(−5)2
⇒[2x−1=52x−1=−5⇒[2x=62x=−4⇒[x=3x=−2⇒[2x−1=52x−1=−5⇒[2x=62x=−4⇒[x=3x=−2
b) 8x3−50x=08x3−50x=0
2x(4x2
a: Ta có: \(\left(2x-1\right)^2-25=0\)
\(\Leftrightarrow\left(2x-6\right)\left(2x+4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)
27.x3=(x+2)3
33.x3=(x+2)3
(3.x)3=(x+2)3
=> 3x=x+2
3x-x=2
x(3-1)=2
x.2=2
x=2:2=1